Disentangling the effects of species interactions and environmental factors on the spatial pattern and coexistence of two congeneric Pinus species in a transitional climatic zone - Yang, Zhichun; Luo, Ying; Ye, Nan; Yang, Lishunan; Yin, Qiulong; Jia, Shihong; He, Chunmei; Yuan, Zuoqiang; Hao, Zhanqing; Ali, Arshad (Ecology and evolution, 2022)
Congeneric species are critical for understanding the underlying ecological mechanisms of biodiversity maintenance. Ecological mechanisms such as conspecific negative density dependence, species differences in life‐history stages related to habitat preference, and limiting similarity are known to influence plant fitness, thereby influencing species coexistence and biodiversity. However, our understanding of these phenomena as they apply to coexistence among coniferous species is limited. We studied two congeneric Pinus species, Pinus armandii (PA) and Pinus tabulaeformis (PT), both of which are common pioneer species typically succeeded by oaks (Quercus), in a 25‐ha warm temperate deciduous broad‐leaved forest. Here, we addressed the following questions: (1) How do population structures and distributions patterns of these two Pinus species vary with respect to different life‐history stages? (2) Does intra‐ and interspecific competition vary with respect to three life‐history stages? And (3) What are the relative contributions of topographic and soil variables to the spatial distributions of the species across the three life‐history stages? In addressing these questions, we utilized the pair‐correlation function g(r), redundancy analysis (RDA), variance partitioning (VP), and hierarchical partitioning (HP) to identify habitat preferences and conspecific negative density dependence at different life‐history stages from small to large trees. The results revealed that in both Pinus species, individuals in different life‐history stages were subject to significant habitat heterogeneity, with a tendency for small trees to be distributed at higher latitudes that may be represents climate‐change‐driven migration in both species. In addition, the effects of conspecific negative density dependence on PT were stronger than those on PA due to limited dispersal in PT. Furthermore, we found that interspecific competition was weak due to the species differences in resource utilization and preference for key habitats. Our study shows that congeneric Pinus species avoids competition by exploiting distinct habitats and provides insight into forest community structure. The results revealed that in both Pinus species, individuals in different life‐history stages were subject to significant habitat heterogeneity, with a tendency for small trees to be distributed at higher latitudes that may be represents climate‐change driven migration in both species. In addition, the effects of conspecific negative density dependence on PT were stronger than those on PA due to limited dispersal in PT. Furthermore, we found that interspecific competition was weak due to the species differences in resource utilization and preference for key habitats.